2022
DOI: 10.3733/ca.2022a0008
|View full text |Cite
|
Sign up to set email alerts
|

Winter flooding recharges groundwater in almond orchards with limited effects on root dynamics and yield

Abstract: California signed the Sustainable Groundwater Management Act (SGMA) into law in 2014. SGMA requires groundwater-dependent regions to halt overdraft and develop plans to reach an annual balance of pumping and recharge. Groundwater aquifers can be recharged by flooding agricultural fields when fallow, but this has not been an option for perennial crops such as fruit and nut trees. While flooding these crops might be possible during the dormant season, it is not known what impact flooding might have on tree-root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We vary the inundation frequency (Table ), though all simulations receive a total of 0.8 m 3 m −2 of water over 1–14 weeks. This inundation volume was chosen based on published values for flood‐MAR projects on almond orchards in the Central Valley: 0.61–0.76 m 3 m −2 (Bachand et al., 2019), 0.76 m 3 m −2 (Ganot & Dahlke, 2021), and 0.60–0.67 m 3 m −2 (Ma et al., 2022; Murphy et al., 2021). The falling head inundation is too computationally expensive to simulate across subsequent flood‐MAR events.…”
Section: Methodsmentioning
confidence: 99%
“…We vary the inundation frequency (Table ), though all simulations receive a total of 0.8 m 3 m −2 of water over 1–14 weeks. This inundation volume was chosen based on published values for flood‐MAR projects on almond orchards in the Central Valley: 0.61–0.76 m 3 m −2 (Bachand et al., 2019), 0.76 m 3 m −2 (Ganot & Dahlke, 2021), and 0.60–0.67 m 3 m −2 (Ma et al., 2022; Murphy et al., 2021). The falling head inundation is too computationally expensive to simulate across subsequent flood‐MAR events.…”
Section: Methodsmentioning
confidence: 99%
“…Since C2Vsim operates on a monthly time step we assume that the recharge water is only available for 5 days ca=1/5 ${c}_{a}=1/5$ each month based on statistical analyses done by Kocis and Dahlke (2017). To estimate the corresponding land area needed to recharge the maximum daily volume we assume, based on field experiments and water availability (Dahlke & Kocis, 2018; Ma et al., 2022), that a maximum water depth of 4.52 m (15 ft) (cb=150.25emft ${c}_{b}=15\,ft$) can be recharged within the winter rainy season (November‐April). As the hydrologic model is too coarse to capture any spatial variability at a field level, the diverted water is spread proportionally to the element area so that the elements that are receiving diversions from the same diversion node have the same rate.…”
Section: Applicationmentioning
confidence: 99%
“…Here, we showed that precipitation events that occur during the wet‐up and the dry‐down display characteristics common to water‐limited systems, whereas precipitation events that occur in the plateau display characteristics common to energy‐limited systems. As human population and thus water demand grows, we have started to manage storm flows through practices such as managed aquifer recharge, where we engineer catch basins to purposefully infiltrate stormflow to manually recharge the subsurface (Levintal et al, 2022; Ma et al, 2022). In water‐limited systems, the standard practice is to remove water in times of surplus (Dahlke et al, 2018).…”
Section: Implications and Conclusionmentioning
confidence: 99%